AB0020B QUANTIFYING DIFFERENCES IN HERITABILITY AMONG PSORIATIC ARTHRITIS (PSA), CUTANEOUS PSORIASIS (PSC) AND PSORIASIS VULGARIS (PSV). (June 2019) - Quan, LI; Chandran, Vinod; Tsoi, Lam; Nair, Rajan; Gladman, Dafna D.; Elder, James T.; Rahman, Proton
Abstract : Background: Epidemiological studies have established a large recurrence risk ratio among siblings suggesting a strong genetic component for psoriasis and psoriatic arthritis (1). Better understanding of the heritability of PsC, PsV and PsA will lead to more efficient genetic profiling for psoriatic disease. Objectives: We set out to assess the heritability of cutaneous psoriasis without known arthritis (PsC); psoriasis vulgaris (psoriasis irrespective of arthritis, PsV) and psoriatic arthritis (PsA) by interrogating SNPs from a large scale genotyping array. Methods: The heritability of PsC, PsV and PsA were estimated by interrogating 715 PsA, 1155 PsC, 2938 PsV patients and 3117 unaffected controls of European ancestry. The samples were genotyped on a custom Axiom Biobank plus genotyping array and core GWAS chip with 461, 092 autosomal SNPs. Further imputation led to 1.3M well-imputed SNPs based on the autosomal reference panel of the HapMap Phase 3 (HM3) CEU cohort. After strict filtering, 230k autosomal SNPs without imputation and 401k autosomal SNPs after imputation were retained for heritability estimation. The following two methods were used to determine the heritability of PsC, PsV and PsA from SNP based data: Linkage Disequilibrium Adjusted Kinships (LDAK) and GCTA which relies on the restricted maximum likelihood algorithm (ReML). Sex and the top 5 principal components were used as covariates to control for gender effect and population stratification in each analysis. Parallel analyses were performed after removing SNPs from the MHC region. The prevalence also was used to adjust the heritability estimation. Results: The heritability assessment for psoriatic disease for each method is presented in the table with and without imputation. Although the heritability estimates vary depending on the method, the heritability of PsC appears to be greater than PsA, for analysis that was done with and without imputation. Similar trends are noted when non-MHC SNPs were assessed. Conclusion: SNP based heritability estimates suggest greater heritability for PsC as compared to PsA. Common environmental factors may need to be considered to account the strong recurrence rate of PsA over psoriasis among first degree relatives reported in previous epidemiological studies, as this finding is not noted from large SNP based association studies. References: [1] Chandran V, Schentag CT, Brockbank JE, Pellett FJ, Shaumugrajah S, Toloza SM, Rahman P, Gladman DD. Familial aggregation of psoriatic arthritis. Ann Rheum Dis. 2009; 68(5):664-7. Disclosure of Interests: Quan Li: None declared, Vinod Chandran: None declared, Lam Tsoi: None declared, Rajan Nair: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen, Celgene, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead, Janssen, Lilly, Novartis, Pfizer, and UCB, James T. Elder: None declared, Proton Rahman: None declared